Performance of family planning clinics in conducting recommended HIV counseling and testing in Mombasa County, Kenya: a cross-sectional study - McKenna C. Eastment; George Wanje; Barbra A. Richardson; Faiza Nassir; Emily Mwaringa; Ruanne V. Barnabas; Kenneth Sherr; Kishorchandra Mandaliya; Walter Jaoko; R. Scott McClelland (BMC, 2019)
Abstract Background A high proportion of African women utilize family planning (FP) services. Accordingly, incorporating HIV testing into FP services may strategically target the first WHO 90-90-90 goal of 90% of people living with HIV knowing their status. Methods The objective of this analysis was to determine the proportion of new FP clients counseled and tested for HIV, as well as correlates of HIV testing, in a random sample of 58 FP clinics in Mombasa County, Kenya. Structured interviews of FP clinic managers collected data on characteristics of FP clinics and staff. Study staff performed a 3-month review of FP registers, summarizing new client HIV testing and counseling (HTC). Because overall rates of HTC were quite low, a binary variable was created comparing clinics performing any HIV counseling and/or testing to clinics performing none. Generalized linear models were used to calculate prevalence ratios (PR) and identify correlates of HTC. Factors associated with any HTC with a p-value < 0.10 in univariate analysis were included in a multivariate analysis. Results Of the 58 FP clinics, 26 (45%) performed any counseling for HIV testing, and 23 (40%) performed any HIV testing. Counseling for HIV testing was conducted for 815/4389 (19%) new clients, and HIV testing was performed for 420/4389 (10%). Clinics without trained HIV testing providers uniformly did not conduct HIV counseling and/or testing (0/12 [0%]), while 27/46 (59%) of clinics with ≥1 provider performed some HTC (p < 0.001). In the subset of 46 clinics with ≥1 trained HIV testing provider, correlates of performing HTC included being a public versus non-public clinic (PR 1.70 95%CI 1.01-2.88), and having an HIV comprehensive care center (CCC) onsite (PR 2.05, 95%CI 1.04-4.06). Conclusion Trained HIV testing providers are crucial for FP clinics to perform any HTC. Approaches are needed to increase routine HTC in FP clinics including staffing changes and/or linkages with other testing services (in standalone VCT services or lab facilities) in order to improve the implementation of existing national guidelines. A future cluster randomized trial is planned to test an implementation strategy, the Systems Analysis and Improvement Approach (SAIA) to increase HTC in FP clinics.